OPTIMIZATION OF ZAKAT, INFAQ, AND DIGITAL ALMS FOR POVERTY ALLEVIATION: ANALYSIS OF DISTRIBUTION EFFICIENCY BY DATA ENVELOPMENT ANALYSIS - Nur Fitry Latief (SOSIOEDUKASI, 2025)
This study analyzes the distribution efficiency of digital zakat, infaq, and sadaqah (ZIS) in Indonesian zakat management institutions using Data Envelopment Analysis (DEA) to measure its contribution to poverty alleviation. Using data from 25 digital LAZs for the 2021-2023 period, this research applies DEA-CCR and DEA-BCC models to measure technical efficiency, scale efficiency, and allocative efficiency. Input variables include collected ZIS funds, digital operational costs, and number of personnel, while outputs encompass number of mustahik served, poverty reduction rate, and program sustainability. Results show only 9 LAZs (36%) achieved full efficiency with an average efficiency score of 0.73, indicating a 37% potential output increase. DEA-BCC analysis identified 14 LAZs (56%) achieving pure technical efficiency, with scale inefficiency as the main source of inefficiency. LAZs with integrated digital fundraising models have 27% higher efficiency. Slack analysis reveals the largest input excess in operational costs (22.6%) and output shortfall in poverty reduction (30.4%). The study recommends scaling up for LAZs with increasing returns to scale, process optimization for decreasing returns to scale, adoption of data analytics, automated distribution systems, and increased proportion of productive programs to maximize poverty alleviation impact.